Quantifying surface roughness on UO2 fuel pellets using optical techniques. (November 2020) - Said, Meena; Eng, Charlotte W.; Hixon, Amy E.; Marks, Naomi E.
Highlights: Surface roughness methods were developed via profilometry and microscopy. 3D measurements provide quicker, more precise values than 2D measurements. Digital microscopy provides higher quality results than profilometry. UO2 pellet surface roughness has potential as a nuclear forensic signature. Abstract: Rapid, non-destructive nuclear forensic techniques can aid in signature development and provide valuable information for provenance assessments. Using optical profilometry and digital microscopy, we studied the surface roughness of fuel pellets to probe its usefulness as a forensic signature and its relationship to a given producer's grinding techniques. Arithmetic average areal (Sa ) surface roughness measurements provide a rapid, non-destructive technique, producing efficient measurements with smaller standard uncertainties relative to 2D, arithmetic average profile (Ra ) surface roughness measurements. Digital microscopy proved to be the superior technique over optical profilometry, in part due to its higher image quality, faster data acquisition capabilities, and multi-purpose potential in physical surface characterization. Using digital microscopy, fuel pellet Sa surface roughness varies in commercial reactor fuel pellets from 1.54 ± 0.17 μm to 2.11 ± 0.12 μm and does not appear to depend solely on the use of wet versus dry grinding techniques. Populations of pellets produced at three different commercial reactor fuel production facilities were distinguishable on the basis of Sa . Complementary to other key forensic characteristics, such as dimensions and enrichment, Sa measurements provide a promising nuclear forensic signature for sintered UO2 fuel pellets.